2008 financial crisis and stock markets intertemporal linkages across Asia and U.S. - Wang, Binzhu (2011)
The 'secret linkages' among stock markets in 1997 Asia financial crisis have all headed above water - the cause and phenomenon, integration and causal linkages across Asian stock markets have been widely studied. While in case of 2008 global financial crisis, no research has been done on examining the intertemporal linkages across stock markets yet.